Democratizing Resource Governance through Prior Consultations? Lessons from Bolivia's Hydrocarbon Sector - Almut Schilling-Vacaflor (German Institute of Global and Area Studies (GIGA), 2012)
With the recent expansion of extractive industries in Latin America, contestations with the affected communities have increased in number and intensity. Therein, the indigenous right to prior consultation and to free, prior and informed consent has played a crucial role. Based on the empirical study of several consultation processes in Bolivia's hydrocarbon sector since 2007 and referring to deliberative theories as well as human rights norms, this article explores the enabling and constraining factors in the democratization of resource governance through these procedures. While the specificities of consultations in plurinational Bolivia are taken into account, the study also draws general conclusions for similar processes in other resource-reliant countries.
Keywords: 300; resource governance; human rights; indigenous peoples; prior consultation; deliberative democracy; Bolivia; Latin America; Governance-Ansatz; Menschenrechte; Indigene Völker; Partizipation; Demokratisierung; Bolivien